Development of T cells in SCID mice grafted with fetal thymus from AKR mice or F344 rats - Maeda, K; Nagasawa, H; Furukawa, A; Hisaeda, H; Maekawa, Y; Manabe, T; Kudo, E; Good, R A; Himeno, K (European journal of immunology, 1993)
To examine the development of T cells within an allogeneic or xenogeneic environment, we engrafted the fetal thymus from AKR mice or F344 rats under the kidney capsule of SCID mice (mTG and rTG mice). T lymphopoiesis developed in SCID mice 2 months after transplantation, although the ratio of CD4/CD8 in both experimental groups was different from that of normal control. T cells in mTG mice did not show in vitro proliferation or cytotoxicity against either host-type C.B-17 (H-2d) or donor-type AKR (H-2k) cells, while they exerted potent activities against third-party B10 (H-2b) cells. In contrast, T cells in rTG mice exhibited proliferation against both host-type C.B-17 and donor-type F344 rat cells. Consistently, graft-vs.-host disease symptoms developed in these mice and histological examination showed impressive infiltration of lymphocytes into the skin or into the mucosal layers of the stomach. Activated state of T cells in rTG mice was also evidence by the positive expression of interleukin-2 receptor. Taken together, fetal thymus appears to contain progenitor cells which are sufficient for in vivo reconstitution of T lymphopoiesis, but species-specific environment is important for the induction of tolerance. In mTG mice, V beta 6+ T cells reactive to donor Mlsa determinants and V beta 3+ T cells reactive to host Mlsc determinants were deleted, suggesting that tolerance was regulated mainly by clonal deletion. By contrast, V beta 11+ T cells reactive to Mlsf determinants were not deleted possibly due to the lack of their ligands.